Microwave engineering : - Nair, B. Somanathan (Sanguine Technical Publishers, 2005)
This book gives detailed explanations of several microwave active and passive devices, such as klystrons, magnetrons, TWTs, BJTs, Gunn diodes, tunnel diodes, Read diodes, directional couplers, tees, hybrid junctions, etc. Three-dimensional diagrams should be an essential part of any textbook on Microwave Engineering, as they give the reader an actual physical feeling of the situation for (or about) which they are drawn. Therefore, we have included a large number of 3-D pictures. The most important feature of this text is a large number of practical designs that have been given in the chapter on microwave filters. Principles of step-by-step approach have been employed in each of these designs.